Gambaran Sindroma Pasca menopause Pada Wanita Lansia di Panti Werdha Wisma Mulia, Grogol, Jakarta - Cipta Pramana; Angeline Vincentia; Andriana Kumala Dewi (JURNAL KESEHATAN REPRODUKSI, 2021)
ABSTRACTBackground: The number of elderly women will continue to increase along with the high life expectancy. The decline in estrogen and progesterone after menopause causes direct effects in the form of physical and psychological disorders.Objectives: This study aims to describe the symptoms of postmenopausal syndrome in the elderly.Method: Non-probability descriptive sampling method has been carried out in the elderly group of women (N=38). Interviews based on the Guide to Greene Climacteric Scale questionnaire were conducted to collect data.Results and Discussion: Overall, postmenopausal syndrome was experienced by 79.47% of respondents. A total of 26.32% of respondents were very disturbed by anxiety symptoms. 34.21% and 39.47% of respondents were slightly disturbed by depressive and somatic symptoms. Only 5.26% of respondents were very disturbed by the symptoms of sexual dysfunction. Subjects with low education have a risk of 7.8 times experiencing symptoms of postmenopausal syndrome compared to subjects with higher education. Subjects who were nullipara had 2.6 times the risk of experiencing symptoms of postmenopausal syndrome when compared to primi/multipara.Conclusion: More than half of the respondents experienced postmenopausal syndrome, either in the form of symptoms of anxiety, depression, somatic, vasomotor, or sexual dysfunction. Subjects with low education have a higher risk of experiencing postmenopausal syndrome than those with low education.Keywords. Menopaus;  elderl;  postmenopausal syndrome.